PTU-038 Long term follow-up of patients with non-alcoholic steatohepatitis. (28th May 2012) - Lafferty, H; Evans, C D; Oien, K A; Mills, P R
Abstract : Introduction: Non-alcoholic steatohepatitis (NASH) is an increasingly common cause for liver disease. More evidence is needed to determine the natural history and prognosis of this condition. The aim of the study was to conduct a prospective follow-up of a group of patients with NASH confirmed on liver biopsy over a period of up to 26 years. Methods: A study of 62 patients who had NASH on liver biopsy performed during the period 1985 to 1994 was published in 2002. 1 Biopsies were scored according to Brunt's system 2 by a single pathologist. 59 of these patients were now traceable. Information on long-term outcome was obtained by review of case notes, electronic patient records and data from NHS Information Services Division and the Registrar General for Scotland. Follow-up duration was defined as the time between diagnosis by initial liver biopsy and last hospital attendance or death. 1 patient subsequently tested positive for hepatitis C and was excluded from further analysis. Results: 17 of the 58 patients were male, with an overall mean age at diagnosis of 44 (range 17–74 years). 56 were Caucasian and 2 Asian and mean follow-up in years was 15 (range 0–26). Mean body mass index at diagnosis was 27.6 (range 21.1–41.3). At diagnosis, 6 (10.3%) had diabetes mellitus (DM), 14 (24.1%) hypertension (HTN) and 4 (6.9%) ischaemic heart disease (IHD). On follow-up a total of 21 (36.2%) patients had a diagnosis of DM and 30 (51.7%) HTN. On initial biopsy none of the patients had cirrhosis. During follow-up 15 (25.8%) patients developed cirrhosis (3 biopsy proven and 12 clinical). 5 (8.6%) patients developed hepatic decompensation with jaundice (2), ascites (2), encephalopathy (1), variceal haemorrhage (1) and hepatoma (1). 28 (48.3%) of the patients have died at a mean age of 70.4 years (range 33–97). Time to death from diagnosis was 0.5 to 24 years (mean 14). Two patients died of liver failure (7.1%), 4 from non-hepatic malignancy (14.3%), 6 from IHD (21.4%), 3 of infectious causes (10.7%), 3 of cerebrovascular disease (10.7%) and 10 of "other causes" (2 chronic obstructive pulmonary disease, 1 DM, 1 alcohol, 1 pancreatitis, 5 unknown). Conclusion: This observational study shows that the outcome of NASH is not benign with a significant mortality over a mean of 15 years, largely due to vascular disease and malignancy as expected. Progression to cirrhosis occurred in 26% of patients causing considerable clinical morbidity, but death from liver disease over this time period was uncommon. Competing interests: None declared. References: 1. J Clin Path 2002;55 :689–692. 2. Am J Gastroenterol 1999;94 :2467–74.